2021
DOI: 10.1016/j.ajo.2020.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Persistence, and Performance of Weekly Home Monitoring of Visual Field in a Large Cohort of Patients With Glaucoma

Abstract: Uptake, persistence, and performance of weekly home monitoring of visual field in a large cohort of patients with glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(78 citation statements)
references
References 23 publications
7
70
0
1
Order By: Relevance
“…Our findings are consistent with other studies evaluating perimetry through non-conventional means, such as tablets, personal computers, or virtual reality headsets. Tablet perimetry has good reliability and repeatability, and is useful for home-perimetry; however one potential disadvantage is access to hardware [ 35 , 36 ]. Computer-based standard white-on-white perimetry has been previously reported with good validity compared to conventional white-on-white perimetry [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other studies evaluating perimetry through non-conventional means, such as tablets, personal computers, or virtual reality headsets. Tablet perimetry has good reliability and repeatability, and is useful for home-perimetry; however one potential disadvantage is access to hardware [ 35 , 36 ]. Computer-based standard white-on-white perimetry has been previously reported with good validity compared to conventional white-on-white perimetry [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not believe that this will be the case as we have reported similar outcomes in a glaucoma cohort that did not have a history of clinical trial exposure. 24 Several methods are presently available for monitoring iAMD patients and these include visual acuity, hyperacuity, Amsler grid and DLS with free-viewing perimetry. Loss of visual acuity has a poor correlation with anatomical changes observed in early AMD 17 and the Amsler grid has a reported sensitivity of 30% for detecting choroidal neovascularisation (CNV).…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently investigated the application of MRF in the home monitoring of glaucoma patients where we found a weekly compliance of 72% over a 6-week period. 24 Given this promising result, we wished to evaluate the application of home monitoring on a weekly basis to patients with high-risk early stages of AMD. AMD typically affects people aged 50 and over, thus there could be technological challenges in operating the application.…”
Section: Introductionmentioning
confidence: 99%
“…32 Participants were recruited from clinics and had detailed ophthalmological examinations, except in 5 studies 24,32,34,40,41 where examinations were not reported. Three studies 25,28,32 included patients with glaucoma or ocular hypertension, 11 studies 24,26,27,[29][30][31]33,[36][37][38]41 included glaucoma patients and healthy controls, 3 studies 35,39,40 also included patients with other diagnosis, and 1 study 34 did not specify participant diagnosis.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%